Live unilateral tubal pregnancy: a case report - Tiwary, Rimple; Tiwary, Manish Kumar (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2023)
The pain in the abdomen during pregnancy presenting to the emergency department (ED) is a big diagnostic challenge. A pregnancy that occurs most commonly in the fallopian tube, outside of the uterus is known as ectopic pregnancy. Acute appendicitis and ectopic pregnancy are the two most common causes of pain in the abdomen during pregnancy presenting to the emergency department. At 11 weeks of gestational period, 27-years-old gravida 2 para 1 presented with a 3-day history of right iliac fossa pain which was not associated with vaginal bleeding, fever, diarrhea, and vomiting. The vitals were stable on general examination. There was mild tenderness and guarding at the lower abdomen. An elevated beta-human chorionic gonadotrophin (βhCG) levels, cervical motion tenderness on digital vaginal examination, and transvaginal ultrasonography found a single live gestation with fetal heartbeat of 170 beats/min and a single placenta. The right live tubal ectopic pregnancy was diagnosed in the patient. Open right salpingectomy was performed on the patient. The patient remained stable in the postoperative period and was discharged uneventfully from the hospital.